Aplikasi Teknologi Bioflok pada Pemeliharaan Benih Ikan Betok (Anabas testudineus) dengan Padat Tebar Berbeda - Fitrani, Mirna; Putra, Andy Candra; Yulisman, Yulisman (Jurnal Perikanan dan Kelautan, 2015)
Climbing perch is one of fresh water fish that has been started to be cultured, howeverthere are some problems occur such as low growth rate and high price of feed. Biofloc is atechnology that use bacteria which is able to destroy the waste and to maintain the water quality.Floc can be used as feed as well. This technology is capable to be applied even in the highdensity of fish rearing.T he aim of this research was to study the effect of biofloc technologyfor climbing perch culture with different densities. This research was conducted in the Muliasarivillage, Banyuasin District, South Sumatera Province since February to April 2015. TheCompletely Randomized Design (CRD) with five treatments and three replications wasapplied. The treatments were A : 100 fish/m2of density without biofloc technology, B : 100fish/m2of density with biofloc technology, C : 200 fish/m2of density with biofloc technology,D : 300 fish/m2of density with biofloc technology, E : 400 fish/m2of density with biofloctechnology. Results shown that the addition of biofloc provide significantl effect on floc, fishgrowth and feed conversion ratio. The best density was 400 fish/m2 with 5.8 mL/L of floc andfood conversion ratio 0.81, survival rate 73%, growth weight 2.77 gram and legth of 1.87 cm.